PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA SISTEM PERSAMAAN LINEAR DUA PEUBAH DI MTS RAUDHATUL HASANAH MEDAN - Solahuddin Al'Ayyubi Dalimunthe; E Elvis Napitupulu (Universitas Negeri Medan, 2015)
AbstractThe purpose of this study was to determine the increase in student learning outcomes on the subject of the system of linear equationswith two variables cooperative learning Numbered Head Together. Subjects in this study were class VIII-2 MTs Raudhatul Hasanah many as 31 people. The object of this research is the application of the cooperative model Numbered Head Together. The research instrument used by observation and tests. This type of research is a classroom action research. Before giving action, first given a diagnostic test to determine the ability and determination of the initial group of students based on ability level. The data provided in the form of shaped achievment test descipsion given twice at the end of each cycle. In this study the use of worksheets intended as teachingn tool to facilitate teaching and learning in cooperative groups. From the analysis of the data after a given action I (cycle I) obtained 23 out of 31 student (74,19%) reached mastery learning and 8 out of 31 students (25,80%) has not reached mastery learning with an average grade 68,70. In this cycle of learning completeness in classical yet achieved. From the analysis of the data after a given action II (cycle II) obtained 27 out of 31 students (87,10%) reached mastery learning, and 4 out 31 students (12,90%) has not reached mastery learning with an average grade 77, 09. In this cycle of learning completeness classically been reached. This means that an increase in student learning outcomes from cyle I to cycle II. Thus the implementation of cooperative learning model Numbered Head Together can improve student learning outcomes on the subject of the system of linear equations in two variables of class VIII MTs Raudhatul Hasanah.Keywords : Cooperative, Numbered Head Together, Raudhatul Hasanah